Граничное поведение решений линейных параболических уравнений второго порядка - Скрыпник, И.И. (Український математичний журнал, 1993)
Properties of solutions of parabolic equations in smooth cylindrical domains are studied. Conditions for existence of boundary non-tangents and L₂-limits as t→0 are found.